2009
DOI: 10.2967/jnmt.109.065847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proton Pump Inhibitors and H2 Antagonists on the Stomach Wall in 99mTc-Sestamibi Cardiac Imaging

Abstract: On the basis of previously unpublished observations, we hypothesized that prolonged use of proton pump inhibitors (PPIs) causes an increase in 99m Tc-sestamibi uptake in the stomach wall, manifested as curvilinear activity surrounding the photopenic fundus of the stomach cavity. We prospectively evaluated the frequency of stomach wall uptake in patients undergoing myocardial perfusion SPECT who were taking PPIs or H 2 antagonists. Methods: Patients (n 5 138) who were scheduled for single-day rest/stress 99m Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Attenuation artifacts are a problem in the accurate evaluation of myocardial perfusion scintigraphy. The left anterior-lateral attenuation artifact depending on breast tissue in female and inferior walls attenuation artifact due to diaphragm in men can lead to false positive evaluation on myocardial perfusion SPECT [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation artifacts are a problem in the accurate evaluation of myocardial perfusion scintigraphy. The left anterior-lateral attenuation artifact depending on breast tissue in female and inferior walls attenuation artifact due to diaphragm in men can lead to false positive evaluation on myocardial perfusion SPECT [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Increased gastric wall radiotracer activity (GWA) on SPECT myocardial perfusion imaging studies (MPI), as opposed to the more common hepatobiliary activity and reflux of activity into the stomach, is not well studied and appears to be uncommon, but can interfere with image interpretation. [1][2][3][4][5][6] GWA can lead to false positive or false negative MPI results through overlap with the inferior left ventricle, amplified by the effect of Compton scatter and ramp filtering. The association of gastric wall activity and proton pump inhibitors has been described by several authors previously, although possible mechanisms have been untested, and selection bias has been considered possible.…”
mentioning
confidence: 99%
“…The association of gastric wall activity and proton pump inhibitors has been described by several authors previously, although possible mechanisms have been untested, and selection bias has been considered possible. [1][2][3][4][5][6] While a great many patients referred for SPECT MPI testing take proton pump inhibitors, this interfering activity seems to occur in the minority of them, and it appears to be a clinical problem in fewer still. Nevertheless, the images of occasional patients might be affected severely.…”
mentioning
confidence: 99%
“…The uptake mechanism of 99m Tc-tetrofosmin in gastric tissue is unknown. Some have suggested that 99m Tc-sestamibi localizes in the mitochondria of parietal cells and is excreted via the H 1 /K 1 /adenosine triphosphatase pump into the gastric lumen (5,6), and it has therefore been hypothesized that 99m Tc-tetrofosmin may localize in a similar manner (6).…”
mentioning
confidence: 99%